The effects of explicit vocabulary instructions on secondary ESL students’ vocabulary learning - Mohd Haniff Mohd Tahir,; Intan Safinas Mohd Ariff Albakri,; Airil Haimi Mohd Adnan,; Rafidah Abd Karim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study intends to investigate the effect of explicit vocabulary instructions on students’ vocabulary learning in Perak. A quasi-experimental research design was employed, and the scores of the pre- and post-tests were analysed using independent sample t-test, paired sample t-test and descriptive statistics. The score comparison and total improvement scores in percentage were also presented. The questionnaires in the student’s feedback form were analysed descriptively in terms of their mean scores and standard deviation. The qualitative data from the semi-structured students’ interview was transcribed, categorised and coded by using content analysis. The paired sample t-test results were (t=-17.85, df=29, p<.05) for the experimental group and (t=-4.85, df=29, p<.05) for the control group. Based on the results, the experimental and control groups improved significantly (p=.000*) in the post-test with a mean difference of 15.62. Thus, the use of different techniques of the explicit method is effective in helping learners to acquire target words. A longitudinal study is recommended to observe the effects of the explicit method of vocabulary instructions if longer time is given for the learners to learn the target words. Such work will indicate whether longer learning period results in better vocabulary knowledge or not. This research extends value in the field of vocabulary learning because it can be used to carry out further investigations in improving the students' ability to learn new words. A possible global extension of this study should be conducted to further determine the power of explicit or other novel vocabulary approaches in advancing students’ vocabulary prowess.